Use of the Fluorosis Risk Index in a Cohort Study: The Iowa Fluoride Study - Steven M. Levy, DDS, MPH; Liang Hong, DDS, MS, PhD; John J. Warren, DDS, MS; (Blackwell Synergy, 2006)
Several studies have used the Fluorosis Risk Index (FRI) to assess risk factors for dental fluorosis. This study reports fluorosis prevalence estimates in a birth cohort using the FRI in different ways.